STUDI IN SILICO SIFAT FARMAKOKINETIK, TOKSISITAS, DAN AKTIVITAS IMUNOMODULATOR BRAZILEIN KAYU SECANG TERHADAP ENZIM 3-CHYMOTRYPSIN-LIKE CYSTEINE PROTEASE CORONAVIRUS - Dwi Krihariyani Dwi; Retno Sasongkowati; Edy Haryanto (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2020)
The 3-chymotrypsin-like cysteine ??protease (3CLpro) is an enzyme that control replication of the coronavirus life cycle. The 3CLpro is a biological target that will interact with drugs. Brazilein is a major compound found in secang wood that used as an immunomodulator. This study aims to predict the immunomodulatory activity of the brazilein against the 3CLpro using in silico method, with curcumin as comparative compound. In silico test was used to predict immunomodulatory activity by docking using the Molegro Virtual Docke. Receptors used are 3CLpro, PDB code: 6M2N, with ligand 3WL_401[C]. pkCSM online program used to predict pharmacokinetic properties (ADME) and toxicity from brazilein and curcumin. Data was analyzed by comparing the docking bond energy between brazilein, ligands and curcumin at the target receptor. The lower the ligand bond energy, the more stable the bond is formed. The results of the in silico test showed that the ligand bond energy = -83,1153kcal/mol, brazilein = -82.0583kcal/mol, and curcumin = -115.852kcal/mol. Brazilein has lower potential as an immunomodulator than ligands and curcumin. The results of the in silico test using the pkCSM online program showed that the brazilein compound had good pharmacokinetic properties and low toxicity.